Влияние импульсного лазерного воздействия на перераспределение углерода в стали - Величко, И.Г.; Данильченко, В.Е.; Недоля, А.В.; Титов, И.Н. (Видавничий дім "Академперіодика" НАН України, 2008)
The influence of the impulse laser treatment of nickel steels on structure changes in the laser effect zone is investigated. In order to describe the processes of heat- and mass-transfer, a mathematical model is suggested. This model consists of the heat and diffusion problems with taking a nonlinear dependence of the carbon diffusion coefficient on temperature and concentration into account. Distributions of the temperature and concentration fields in the laser effect zone are determined. They well agree with experiment in the first approximation. The explanation of the mechanism of forming the oscillatory carbon concentration distribution over the depth of a sample is proposed.